Uji Efektifitas Ekstrak Tanaman sebagai Nematisida Nabati terhadap Tingkat Fekunditas Nematoda Puru Akar (Meloidogyne Spp.) pada Tanaman Seledri (Apium graveolens L.) di Rumah Kaca - Eaggeliony, Jenifer Christy; Singarsa, I Dewa Putu; Suniti, Ni Wayan (Fakultas Pertanian Universitas Udayana, 2023)
The Effective Test of Plant Extracts as A Nematicide for Fecundity of Root Knot Nematodes (Meloidogyne spp.) in Celery Plant (Apium graveolens L.) at Greenhouse. Root knot nematodes Meloidogyne spp. is among the harmful organism in plant cultivation, one of which is in the celery plant. Nematodes caused drop in/reduced plant productivity and plant quality, it can even lead to death and crop failure. Base on the adverse effects of nematodes attack, it must be anticipated. Biopesticides is one of the alternatives that can be used to suppress the growth of nematodes and more environmentally friendly. The purpose of this study is to know the effectiveness of the plant extracts that suppress the number of egg mass, the number of eggs per egg mass and the number of adult females in 1 g of roots. This study using a completely randomized design (CRD), with 5 types of treatments and each treatments received 5 repetitions. The treatments are by giving each plant extracts of 100 cc per pot. The result showed that the extract of marigold plants (Tagetes spp.) has the highest effectiveness, with the percentage of emphasis on the number of eggmass in 1 g roots is 99%, the emphasis on the number of eggs per eggmass in 1 g roots is 84,6% and the emphasis on the number of adult females in 1 g roots is 99,4%. While extract of sour-plant showed that has the lowest effectiveness, with the percentage of emphasis on the number of eggmass in 1 g roots is 96,68%, the emphasis on the number of eggs per eggmass in 1 g roots is 60,72% and the emphasis on the number of adult females in 1 g roots is 98,44%.